The Effect of the Number and Identification of Recipients on Organ-Donation Decisions - Harel, Inbal; Kogut, Tehila (Frontiers in Psychology, 2021)
We examined how presentations of organ donation cases in the media may affect people’s decisions about organ donation issues. Specifically, we focused on the combined effect of the information about the number of recipients saved by the organs of one deceased person (one vs. four) and the identifiability of the donor and the recipient(s) in organ donation descriptions, on people’s willingness to donate the organs of a deceased relative. Results suggest that reading about more people who were saved by the organs of a deceased donor does not increase willingness to donate. Replicating earlier research, we found that reading about a case of organ donation involving an identified deceased donor, deceased willingness to donate. However, this effect was attenuated when participants read about more recipients who were saved by the donation. Importantly, the presentation that prompted the greatest willingness to donate a deceased relative’s organs was the one that featured an unidentified donor and only one identified recipient. Finally, an explorative investigation into participants’ subconscious thoughts of death following the organ donation story revealed that identifying a deceased organ donor prompts more thoughts of death in the perceiver (regardless of the number of recipients).